Risk factors for hypertension among Ghanaian: Evidence from Ghana demographic and health survey - Dzokoto, Maxwell Kwame; Kpen, Bruce; Adam, Ibrahim; Baafi, Anokye Akwasi (Open Science Journal, 2019)
Background: Hypertension is considered an important challenge in public health due to its high risk of cardiovascular disease, kidney disease and death. Despite interventions aimed at reducing the prevalence of hypertension, it still remains the leading cause of stoke and other related diseases and it accounts for 12.8% of all deaths worldwide. The goal of this paper is to explore factors that influences hypertension among men in Ghana. Knowledge of these factors will help public health practitioners provide targeted interventions which will result in a significant reduction of hypertension among the population. Methods: Data source is a survey aimed at collecting data on the indicators of the millennium development goals. Hypertension was the main outcome. Socioeconomic status (primary exposure variable) as well as other potential determinants were assessed. Analytic techniques included multiple Poisson regression that assessed the effects of potential covariates on hypertension in a hierarchical manner. Crude and adjusted prevalent rate ratios are reported with their corresponding 95% confidence intervals at 5% level of significance. Results: The overall prevalence rate of hypertension among Ghanaian men is 8%. Age was found to be a significant predictor of hypertension. Wealth index is also a significant predictor of hypertension with men in levels 4 and 5 more likely to develop hypertension compared to those belonging to level one after adjusting for other covariates. Men with secondary education were 23% more likely to develop hypertension compared to those with higher education, however those with no formal education were 32% less likely to develop hypertension compared to those with higher education after adjusting for other covariates. After adjusting for other covariates, professionals/technical/managerial workers were 35% more likely to be hypertensive compared to those engaged in farming. Men who visited some health facility within the last six months preceding the study were more likely to be hypertensive against those who did not visit any health facility within the same period. Hypertension is more prevalent among parents who lost two or more children compared to parents who were not bereaved. After adjusting for confounders, men with two or more lifetime partners were 13% more likely to be hypertensive as against those with only one lifetime partners. Conclusion: The rate of hypertension in Ghana is high. Factors such as age, wealth index, occupation, bereavement and number of lifetime partners are significant predictors of hypertension after adjusting for potential covariates.